ASSISTANCE IN THE PREPARATION OF FOOD ORGANIZATION STANDARDS IN THE INTEGRATED TAHFIDZ QUR'AN ISLAMIC BOARDING SCHOOL, ALHIKMAH CIREBON - Sholichin Sholichin; Alina Hizni; Diyah Sri Yuhandini; Abiwardani Sekarningrum; Fadhilah Fadhilah (Jurnal Abdisci, 2025)
Integrated Tahfidz Qur'an Islamic Boarding School (ITQ IBS) Alhikmah Cirebon is one of the participants in the activity School Lunch Program (SLP) organized by the Nutrition Department of the Bogor Agricultural Institute in collaboration with PT Ajinomoto in October 2022 - March 2023. ITQ IBS Alhikmah Cirebon prepares 3,000 portions of food every day for breakfast, lunch, and evening for all students and employees. However, it does not yet have food service standards including menu standards, portion standards, recipe standards, seasoning standards, food ingredient quality standards, and well-documented cooking quality standards. Activities are carried out in three stages: 1). The preparation stage is the preparation of standard food management instruments, 2). The implementation stage is a workshop on preparing food service standards and assistance in preparing food service standards, and 3). The Evaluation stage. The results of the evaluation of the workshop activities revealed that there was an increase in the level of participants' understanding of food management standards by 10 points from 53.75 (pre-test) to 63.75 (post-test), and a book on food management standards was prepared.